Quantification of Rhodojaponin II and Rhodojaponin III in Rat Plasma by Ultra-Performance Liquid Chromatography-Tandem Mass Spectrometry - Cheng Sun; Wanhang Wang; Xi Bao; Dizhong Chen; Shenshen Mei; Jianshe Ma; Xiajuan Jiang (International Journal of Analytical Chemistry)
An ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method was developed to determine the concentrations of Rhodojaponin II and Rhodojaponin III in rat plasma, and their pharmacokinetic profiles were investigated. A UPLC HSS T3 (2.1 mm × 50 mm, 1.8 μm) chromatographic column was employed at a temperature of 40°C. The mobile phase consisted of acetonitrile-0.1% formic acid in water, and a gradient elution method with an elution time of 6 min and flow rate of 0.4 mL/min was utilized for analysis purposes. Methodological investigations were conducted accordingly. The plasma concentrations of Rhodojaponin II and Rhodojaponin III exhibited excellent linearity within the range of 2 ng/mL–1250 ng/mL. Moreover, both intraday and interday precision were below 15%, while accuracy ranged from 88% to 115%. Additionally, matrix effect fell within the range of 90%–110%, and recoveries ranged from 78% to 87%. These results comply with relevant regulations for drug analysis in biological samples. Therefore, this method is deemed suitable for quantifying Rhodojaponin II and Rhodojaponin III levels in rats.